Effect of Wrapping on Post-Tensioned Beams Strengthened with Natural Sisal and Jute FRP Using Finite Element Analysis - D. P. Archana; H. N. Jagannatha Reddy; R. Prabhakar; M. U. Aswath; Basavaraju Paruti (Advances in Civil Engineering)
Existing buildings are retrofitted to formulate them to be more resistant to seismic activity, earth motion, and other natural disasters. Many available reinforced concrete buildings across the globe are in desperate need of rehabilitation, repair, or replacement owing to degradation caused by a variety of reasons such as corrosion, lack of detailing, and failure of beam-column bonding, among others. In the construction sector, fibre reinforced polymer (FRP) composites have been recognized as a potential option for repairing and increasing the strength of existing structures. In this study, comparisons are done in terms of load bearing capability of the beams for configurations between FE model predictions and field data (experimental). To assess the FRP retrofit, structural responses for strengthened and control post tensioned concrete (PTC) beams are compared, with strengthening using various wrapping methods. The load bearing capacities of the beams retrofitted with sisal and jute fibre employing strip and full wrapping procedures around all four sides is increased by 35.55 percent and 42.85 percent for sisal FRP and 7.14 percent and 12.01 percent for jute FRP, respectively, as compared to the control specimen. The FRP retrofit model is expected to result in a considerable increase in structural performance.